Scientific Social Networks as A Subject of Sociological Research: Theoretical And Methodological Aspects - Oleg GRIMOV (Communications of International Proceedings, 2021)
The paper concerns the analysis of scientific social networks as a subject of sociological research. The significant theoretical and methodological foundations and focal points that form the conceptual framework of socio-humanitarian understanding of scientific social networks are given in the paper. Among them, the ambivalence of integration and differentiation processes in scientific social networks, a special status of the categories “group” and “community” under the conditions of social network communication, the complex nature of network and academic mobility, the dialectical unity of individual and collective, a variety of configurations of individual, group and institutional capital, the importance of research emphasis on social actors, their connections and resources are considered. It is concluded that it is necessary to apply these guidelines to direct empirical research of scientific social networks.
Keywords: Scientific Social Networks; Science; Scientific Knowledge; Methodology.